2022
DOI: 10.1002/adfm.202200848
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Energy Density in Continuously Gradient‐Structured All‐Organic Dielectric Polymer Films

Abstract: High‐performance dielectric capacitors are critical for advanced electronics and electrical power systems. Polymeric dielectrics have been widely investigated for using in dielectric capacitors because of their high dielectric constants, flexibility, low density, and easy processability. However, it is still challenging to achieve simultaneous improvements in both energy density and efficiency in these dielectric polymers. Here, we report ferroelectric polyvinylidene‐fluoride‐based all‐organic dielectric polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 67 publications
1
48
0
Order By: Relevance
“…At the same time, due to the simultaneous increase of ε r and E b , enhanced U e was obtained for these composite dielectrics with low content and wide bandgap nanoparticles. 91–97 This may be caused by the significantly enhanced dipole polarization of the matrix and large interface content accompanying the nano-sized particles. However, at present, the research on this type of composite is neither comprehensive nor in-depth, and a reasonable and perfect dielectric theory and model are to be urgently established.…”
Section: The Rising Importance Of the Interface In Polymer Nanodielec...mentioning
confidence: 99%
“…At the same time, due to the simultaneous increase of ε r and E b , enhanced U e was obtained for these composite dielectrics with low content and wide bandgap nanoparticles. 91–97 This may be caused by the significantly enhanced dipole polarization of the matrix and large interface content accompanying the nano-sized particles. However, at present, the research on this type of composite is neither comprehensive nor in-depth, and a reasonable and perfect dielectric theory and model are to be urgently established.…”
Section: The Rising Importance Of the Interface In Polymer Nanodielec...mentioning
confidence: 99%
“…To date, two strategies seem to be effective in enhancing the U e of polymer composites. One is utilizing high-k nanofiller to realize a concurrent increase of ε r and E b , which can be divided into two aspects, synthesizing hybrid high-k nanofiller and designing the hierarchical structure of dielectric films [ 14 16 ]. However, these two approaches both are tanglesome (either in nanofiller synthesis or film fabricating process).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in gradient structure composites, the dielectric mismatch of the macro interface between the adjacent layers leads to charge transfer in the composite film form energy barrier; thus, the insulation and polarization characteristics are improved. 47 It is also confirmed that the dielectric/electrode interface plays a more critical role than the dielectric in restraining the leakage current. 48 For BNNS inverse concentration gradient distribution, a smaller leakage current density is obtained for the component with the smallest TiO 2 gradient span, and the variation of the BNNS gradient span has little effect on the leakage current (Fig.…”
Section: Resultsmentioning
confidence: 82%